2013
DOI: 10.1016/j.molcel.2013.08.048
|View full text |Cite
|
Sign up to set email alerts
|

BID Preferentially Activates BAK while BIM Preferentially Activates BAX, Affecting Chemotherapy Response

Abstract: SUMMARY Apoptosis is a highly regulated form of cell death that controls normal homeostasis as well as the anti-tumor activity of many chemotherapeutic agents. Commitment to death via the mitochondrial apoptotic pathway requires activation of the mitochondrial pore-forming proteins BAK or BAX. Activation can be effected by the activator BH3-only proteins BID or BIM, which have been considered to be functionally redundant in this role. Herein, we show that significant activation preferences exist between these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
193
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(217 citation statements)
references
References 58 publications
19
193
2
Order By: Relevance
“…Moreover, recent mechanistic studies have demonstrated a critical role for Bid in the association of RPA with the ATRIP-ATR complex in response to hydroxyurea (HU)-and UV-induced replication stress (50) and sensitivities of BID Ϫ/Ϫ MEFs (mouse embryonic fibroblasts) to several chemotherapeutic agents (75). Consistent with these studies, our data further support a Bid role in ATR-mediated Chk1 phosphorylation in response to the Top1 poison CPT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, recent mechanistic studies have demonstrated a critical role for Bid in the association of RPA with the ATRIP-ATR complex in response to hydroxyurea (HU)-and UV-induced replication stress (50) and sensitivities of BID Ϫ/Ϫ MEFs (mouse embryonic fibroblasts) to several chemotherapeutic agents (75). Consistent with these studies, our data further support a Bid role in ATR-mediated Chk1 phosphorylation in response to the Top1 poison CPT.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have implicated Bid in mediating DDR signaling (50,58,75). Moreover, recent mechanistic studies have demonstrated a critical role for Bid in the association of RPA with the ATRIP-ATR complex in response to hydroxyurea (HU)-and UV-induced replication stress (50) and sensitivities of BID Ϫ/Ϫ MEFs (mouse embryonic fibroblasts) to several chemotherapeutic agents (75).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, microarray analysis identified that upstream BID expression levels were increased, which was corroborated at the protein level. As an essential apoptosis-associated protein, BID may be cleaved into tBID, which then activates Bax and Bcl-2 antagonist/killer, triggering the mitochondrial apoptosis pathway (14)(15)(16). The results suggest a mechanism that may underlie the DESI-2-induced apoptosis observed in our previous study (11).…”
Section: Discussionsupporting
confidence: 56%
“…Bim down-regulation by siRNA completely blocks human gzmB-induced apoptosis. Bim is a BH3-only member of the Bcl-2 family, which has been shown to activate Bak and/or Bax directly, independent of other BH3-only proteins like Bid (23)(24)(25). The combined studies suggest that caspase-3 and Bid are not the only intracellular targets of gzmB (26).…”
Section: Our Results Suggest That the Various Molecular Events Leadinmentioning
confidence: 99%